Haemato-biochemical profile, mineral and electrolyte concentration, and antioxidant status of Zobawng cattle of Mizoram - RAJESH, J B; CHETHAN, G E; ALI, M AYUB; GALI, J M; SARMA, K; KALITA, G; BEHERA, S K; BEHERA, P (The Indian Journal of Animal Sciences, 2020)
Blood biochemical profile plays a pivotal role in assessing health status of animals. The present study was conducted to evaluate haematological and biochemical parameters, trace element and electrolyte concentration, oxidant and antioxidant status in local cattle (Zobawng) of Mizoram. The values recorded for Hb (12.61±0.40 g/dL), RBC (9.10±0.50 106/μL), WBC (11.52+1.13 103/μL), PCV (43.36±0.99%), total protein (8.30±0.17 g/dL), globulin, BUN (10.68±0.68 mg/dL) were on higher side than the exotic cattle breeds. Creatinine (1.96±0.10 mg/dL) and GGT (19.22+1.29 U/L) were also towards upper limit. Calcium (9.78+0.13 mmol/ L), magnesium (2.43+0.07 mmol/L) and inorganic phosphorus (6.76+0.27 mmol/L) values were higher than the exotic breeds and also higher than the Indian Zebu cattle. Total antioxidant was higher and the oxidative stress index was lower as compared to the crossbred or exotic cattle. This study provides first insight into the blood biochemistry of these indigenous cattle indicating its higher disease resistance and will be useful for its better management.